Faktor-Faktor Yang Mempengaruhi Identification, Brand Community, Loyalty Dan Word Of Mouth Pada Produk Zara - Nora Anisa Sinulingga (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
AbstractThe purpose of this study was to analyze the effect of self-identification on social identification and how both of these two variables influenced brand community , this study also seek to find and the influence of brand community on loyalty and word of mouth and the impact from loyalty on word of mouth The conceptual framework consists of the following constructs: self identification, social identification, brand community, loyalty and word of mouth. Six hypotheses tested in this study . Instrument test of validity and reliability used to test the validity of the measures, while structural equation model was used in hypotheses testing. Data were collected from 150 respondents who had been to Zara Store and buy Zara Product. The results showed that self identication has a positive influence on social identification and brand community and social identification also has an influence on brand community. Meanwhile, the brand community has a positive influence on loyalty and word of mouth. The results also show that loyalty does not have a positive influence on word of mouth. Keywords : Self identification, social identification, brand community, loyalty, word of mouth